Bladder augmentation in children and young adults: a review of published literature. Issue 2 (25th May 2015) - Doyle, Sarah; Carter, Bernie; Bray, Lucy; Sanders, Caroline
ABSTRACT: The objective of this study is to review published literature on bladder augmentation in children and young adults (C&YA) with a neuropathic bladder following a neural tube defect or spinal cord injury to inform nursing practice and patient education. Medline, Embase, CINAHL, PsycINFO and the British Nursing Index were systematically searched to identify studies. The papers reviewed were case studies and medical note review in single centres regarding outcome and post‐operative complications. This limits the generalisability of the findings surrounding outcome and risk of bladder augmentation surgery in C&YA. Evidence suggests irrigation has a role in ongoing bladder management to reduce complications such as bladder calculi. However, data are sparse regarding both appropriate irrigation solutions and the frequency of irrigation necessary to minimise calculi formation. A statistically significant increase is noted in the risk of perforation following bladder augmentation when associated with bladder neck surgery at the time of primary surgery. Limited evidence exists regarding longer term systemic implications of bladder augmentation, such as malignancy or impact on bone mineral density. None of the studies demonstrated an overall improvement in health‐related quality of life (HRQoL) following bladder augmentation. Discrepancies exist between parental and children's HRQoL scores. Bladder augmentation is clinically the standard surgical treatment used to manage refractory neuropathic bladder. However, current evidence demonstrates no improvements to HRQoL following surgery and also describes various complications. Future research in this area is necessary to explore standards of care and most importantly long‐term outcome measures from the patient and professional perspective.